Development of Learning Media for Wave Ripple Tanks with the Implementation of Guided Inquiry Models on Students' Mastery of Concepts and Scientific Creativity - Susilawati Susilawati; Aris Doyan; Ahmad Harjono (Postgraduate, University of Mataram, 2022)
The purpose of this study was to develop learning media for wave ripple tanks with the implementation of guided inquiry models on the conceptualization and creativity of students in physics subjects in class XI with the material of mechanical wave characteristics. The wave ripple tank learning media is used as a tool in the learning process that can improve students' mastery of concepts and creativity. This study uses the Research and Development method with a 4D design (Define, Design, Development, Disseminate). At the defining stage, the initial analysis was carried out, namely examining the background behind the emergence of researchers' ideas. The design stage is carried out by designing the wave ripple tank learning media with the implementation of guided inquiry models. The development stage is a development activity as well as an assessment of the experts which includes the validation test of the development results of the device, media ripple tank learning, and assessment instruments. The last stage is the dissemination stage, where the results of this study are distributed to schools to be used as a model that can be used